Mucosa-associated lymphoid tissue (MALT) lymphoma as an unusual cause of malignant hilar biliary stricture: a case report with literature review. Issue 1 (December 2016) - Park, Yong; Choi, Jee; Jung, Woon; Song, Sung; Lee, Jong; Chung, Chul-Woon
Abstract Background Biliary strictures at the hilum of the liver arise from heterogeneous etiologies. The majority is malignant entities, but some may have benign etiologies. It is difficult to distinguish between malignant and benign biliary strictures preoperatively. It has been reported that 5~15 % of preoperative diagnoses of hilar cholangiocarcinoma turn out to be benign lesions or even other types of malignancies. Primary non-Hodgkin's lymphoma of the extrahepatic bile duct is very rare, with only a few cases reported as mucosa-associated lymphoid tissue (MALT) lymphoma arising from the hepatic duct bifurcation. We herein report a case of a female patient presenting with perihilar bile ducts obstructed by primary MALT lymphoma resembling hilar cholangiocarcinoma, along with a review of the literature. Case presentation An 86-year-old female was referred to our hospital manifesting obstructive jaundice and abdominal pain. The reported imaging studies revealed distended intrahepatic bile duct with the stricture of common hepatic duct including bifurcation, which was suspicious of cholangiocarcinoma of the bile duct. The initial laboratory-confirmed cholestasis with a total bilirubin of 8.6 mg/dL, aspartate amino transferase (AST) 178 U/L, alanine transferase (ALT) 105 U/L, and the tumor marker CA 19-9 was elevated with a value of 167 U/mL. Viral markers for hepatitis B and C viruses were negative. She underwent extrahepatic bile duct resection and hepaticojejunostomy. Histological examination of the resected specimen revealed MALT lymphoma. Postoperative follow-up of 1 year has been completely uneventful, without any symptoms or disease recurrence. Conclusions In exceptional cases, in which radiologic and clinical features point to cholangiocarcinoma, the actual reason for obstructive jaundice and abdominal pain can be a non-Hodgkin's lymphoma. In the case of a MALT lymphoma, it can be cured with complete resection.